Management of ileus and small‐bowel obstruction following benign gynecologic surgery. Issue 1 (17th January 2013) - Allen, Arielle M.; Antosh, Danielle D.; Grimes, Cara L.; Crisp, Catrina C.; Smith, Aimee L.; Friedman, Sarah; Mcfadden, Brook L.; Gutman, Robert E.; Rogers, Rebecca G.
Abstract: Objective: To describe practice preferences for the diagnosis and management of ileus and small‐bowel obstruction (SBO) following benign gynecologic surgery. Methods: A secondary descriptive analysis was performed on data from a multicenter case–control study of patients who underwent gynecologic surgery and subsequently developed ileus or SBO. Information was collected regarding interventions such as type of imaging ordered for diagnosis, diet alterations, antiemetic administration, and need for reoperation. Results: In total, 144 cases were identified. Abdominal X‐ray was the most common imaging modality, occurring in 54 (37.5%) cases. Sixty‐nine (65.1%) of the 106 women who underwent imaging were given definitive radiologic diagnoses of either ileus (50 [72.5%]) or SBO (19 [27.5%]); 57.9% (n = 11) of the SBO diagnoses and 90.0% (n = 45) of the ileus diagnoses were managed conservatively. Eighteen (12.5%) patients underwent reoperation for bowel obstruction. There were no significant differences in rate of reoperation between cases involving the use of single antiemetics and those involving the use of multiple antiemetics ( P = 0.18), or between diet statuses on postoperative day 1 ( P = 0.08). Conclusion: Most study centers initially performed an abdominal X‐ray for diagnostic purposes. The majority used a multimodal treatment approach. None of the management options decreased the likelihood of reoperation.